Timing and predictors of disease incidence among named contacts of reported tuberculosis patients in a low incidence setting - Michael Asare-Baah; Lori Johnston; Lina Dominique; Michael Lauzardo; Marie Nancy Séraphin (PLoS ONE, 2025)
Contact investigations are crucial for tuberculosis (TB) control, yet the temporal dynamics of disease progression among exposed contacts remain poorly understood. We conducted a retrospective cohort study of 44,106 contacts linked to 6,243 index TB cases diagnosed between 2009 and 2023. During the 15-year follow-up, 454 contacts developed TB disease, with 43.4% being incident cases. Using time-to-event analysis with left truncation to account for varying follow-up times, and mixed effect Cox models to account for index case and county-level variability, we estimated the median time to TB incidence at 11 (IQR 4–48) months after initiating contact investigation. The risk of TB disease varied markedly by age and immune status. Children aged 0–15 showed over nine times higher risk compared to adults aged 25–44 (aHR = 9.59; 95% CI: 3.17–29.02; p < 0.001). Contacts co-infected with HIV demonstrated a three-fold increased risk of TB (aHR = 2.35; 95% CI: 1.08–5.10; p = 0.031) relative to those without HIV. A history of a previous TB diagnosis conferred a protective effect on the risk of TB incident (aHR = 0.40; 95% CI: 0.20–0.80; p = 0.009). Additionally, individuals who had incomplete therapy for latent TB infection (LTBI) also experienced a protective effect (aHR = 0.32; 95% CI: 0.15–0.71; p = 0.005). These findings highlight a critical window for intervention with follow-up needed for at least 1–4 years after initial contact investigations. The results also emphasize the need for targeted, risk-stratified surveillance and LTBI treatment for children and individuals with HIV who are contacts of confirmed TB cases.